Collins COBUILD illustrated intermediate dictionary of English - Sinclair, John (The COBUILD series, 2013)
Helps learners to develop fluency by providing alternatives to the 50 over-used words in English. This title includes mobile app for the iPhone, Android, and mobile web browsers that allows you to access definitions and examples, and hear pronunciation quickly